Sirt3 Protects Against Thoracic Aortic Dissection Formation by Reducing Reactive Oxygen Species, Vascular Inflammation, and Apoptosis of Smooth Muscle Cells - Qiu, Lin; Yi, Shaolei; Yu, Tingting; Hao, Yan (Frontiers in Cardiovascular Medicine, 2021)
Sirtuin3 (Sirt3) is a histone deacetylase involving in the regulation of many cellular processes. Sirt3 deficiency is known to increase oxidative stress. Reactive oxygen species (ROS) promote degradation of the extracellular matrix and vascular smooth muscle cell (VSMC) apoptosis. Reducing oxidative stress by Sirt3 overexpression could have therapeutic potential for limiting thoracic aortic dissection (TAD) development. We hypothesized that Sirt3 deficiency could increase the risk for TAD by decreasing ROS elimination and that Sirt3 overexpression (Sirt3OE) could provide an alternative option for TAD treatment. Mice with TAD had significantly lower Sirt3 expression than normal subjects. Sirt3 KO mice exhibits significantly increased TAD incidence rate and increased aortic diameters. Moreover, Sirt3 overexpression reduced Ang II-induced ROS production, NF-kB activation, and apoptosis in human aortic smooth muscle cells (HASMCs). Sirt3 overexpression attenuated aneurysm formation and decreased aortic expansion. In conclusion, our data showed that Sirt3 deficiency increases susceptibility to TAD formation by attenuating anti-ROS effects and increasing VSMC apoptosis and vascular inflammation.